Use of forest plantations in Imbabura, Ecuador - Tituaña Armas, Magaly Lisseth (2019)
The analysis of the forest use of cultivated forests (forest plantations) in the province of Imbabura consisted of determining the most used species based on the volume of wood extracted, the cantons with the highest concentration of plantations and the dynamics of exploitation by species, which will allow the approach of local policies to promote the sustainability of forest production in Imbabura, an activity that constitutes an important contribution to the microeconomics of the province because it involves several actors within its productive chain, directly and indirectly. The study was carried out in the province of Imbabura, located in northern Ecuador, and information collected in the forest harvesting programs was analyzed in a period of four years between 2015 and 2018, data provided by the Technical Office of Forest Produc- tion of the District Department of Imbabura of the Ministry of Agriculture and Livestock. An average of 547 hectares have been used annually since 2015, mainly in the Otavalo and Ibarra cantons, the most demanded species are Eucalyptus and Pine. In Imbabura for forest exploita- tion, seven types of actors are involved, 84% of the producers who used cultivated forests, and have a plantation area ofless than five hectares. Forest use since 2010 has tripled in Imbabura, and from 2015 to 2018 it has generated approximately three million dollars for the sale of standing timber, which indicates its contribution and socio-economic importance.